2007
DOI: 10.1002/adma.200701495
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Rechargeable Magnesium Battery Technology

Abstract: Rechargeable magnesium batteries were first presented about seven years ago. [1][2][3] Their components included magnesium metal or a Mg alloy anode, Mg x Mo 6 S 8 (0 < x < 2) Chevrel phase cathodes, and electrolyte solutions that contained an ether solvent and a complex electrolyte, a product of the reaction between a MgBu 2 Lewis base and an AlCl 2 Et Lewis acid (Bu = butyl, Et = ethyl). These systems, while demonstrating impressive cycleability, suffered from several drawbacks:i) The micrometric size Mg 0-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
426
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 497 publications
(441 citation statements)
references
References 21 publications
(36 reference statements)
7
426
1
7
Order By: Relevance
“…1(a)], a conductivity of 5 mS/cm (30°C) and a cycling efficiency of almost 100%. [22] Spectroscopic analysis revealed that these solutions contain multiple species, including MgCl + , Mg 2 Cl 3 + as electrochemical active species, Ph n AlCl 4−n − (n = 1-3), MgCl 2 , Ph 2 Mg, and PhMgCl resulting from various transmetalations of the ligands and the Schlenk equilibrium [ Fig. 1(b)].…”
Section: Challenges and Advances In The Development Of Magnesium Elecmentioning
confidence: 99%
“…1(a)], a conductivity of 5 mS/cm (30°C) and a cycling efficiency of almost 100%. [22] Spectroscopic analysis revealed that these solutions contain multiple species, including MgCl + , Mg 2 Cl 3 + as electrochemical active species, Ph n AlCl 4−n − (n = 1-3), MgCl 2 , Ph 2 Mg, and PhMgCl resulting from various transmetalations of the ligands and the Schlenk equilibrium [ Fig. 1(b)].…”
Section: Challenges and Advances In The Development Of Magnesium Elecmentioning
confidence: 99%
“…For applications, see: Suresh et al (2008); Aurbach et al (2007). For the syntheses and crystal structures of Chevrel phases with various cations, see : Salloum, Gautier et al (2004) ;.…”
Section: Related Literaturementioning
confidence: 99%
“…The classical Chevrel phases, containing blocks of Mo 6 X 8 , have been in interest for both structural respects and application to rechargeable batteries (Suresh, et al, 2008;Aurbach, et al, 2007). The new Chevrel phases In x Mo 15 Se 19 (x=2.9 and 3.3) also have been studied by X-ray single-crystal method (Grüttner et al, 1979).…”
Section: S1 Commentmentioning
confidence: 99%
“…High specific energy density is an essential factor for EV applications, and can be realized by increasing voltage or/and capacity. Recently, new rechargeable batteries with high theoretical specific energy density like air-metal batteries (Kraytsberg & Ein-Eli, 2011;Kumar et al, 2010) and multivalent cation batteries (Mizrahi et al, 2008;Aurbach et al, 2007;Jayaprakash et al, 2011) have attracted attention. Both batteries have lower theoretical electromotive force than LIBs, but they have much higher theoretical specific capacity than LIBs, greatly improving specific energy density.…”
Section: Introductionmentioning
confidence: 99%
“…Both batteries have lower theoretical electromotive force than LIBs, but they have much higher theoretical specific capacity than LIBs, greatly improving specific energy density. Magnesium is being investigated as a promising negative electrode active material for multivalent cation batteries because it has larger specific capacity and is easy to handle and abundant on the earth (Mizrahi et al, 2008;Aurbach et al, 2007).…”
Section: Introductionmentioning
confidence: 99%